Challenges in the comparative study of empathy and related phenomena in animals. (May 2020) - Adriaense, J.E.C.; Koski, S.E.; Huber, L.; Lamm, C.
Highlights: Literature on comparative empathy and related phenomena is critically reviewed Theoretical models should distinguish between distinct empathy related phenomena Empirical findings are more ambiguous than previously presented The emotional basis of these phenomena needs greater attention, particularly valence A multi-component model captures this emotional basis beyond behavior alone Abstract: The aim of this review is to discuss recent arguments and findings in the comparative study of empathy. Based on a multidisciplinary approach including psychology and ethology, we review the non-human animal literature concerning theoretical frameworks, methodology, and research outcomes. One specific objective is to highlight discrepancies between theory and empirical findings, and to discuss ambiguities present in current data and their interpretation. In particular, we focus on emotional contagion and its experimental investigation, and on consolation and targeted helping as measures for sympathy. Additionally, we address the feasibility of comparing across species with behavioural data alone. One main conclusion of our review is that animal research on empathy still faces the challenge of closing the gap between theoretical concepts and empirical evidence. To advance our knowledge, we propose to focus more on the emotional basis of empathy, rather than on possibly ambiguous behavioural indicators, and we provide suggestions to overcome the limitations of previous research .